CROSS-CULTURAL ETHNOMATHEMATICS IN SOUTHEAST ASIA: MATHEMATICAL PRACTICES EMBEDDED IN INDONESIAN AND THAI CULTURAL PHENOMENA - Jaka Wijaya Kusuma; Hamidah; Saran Chantarasri (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study explores cross-cultural ethnomathematical practices embedded in cultural phenomena across Southeast Asia, with a focus on Indonesia and Thailand. The primary objective is to identify and analyze mathematical practices inherent in various cultural aspects, including batik motifs, traditional house architecture, and traditional games in Indonesia, as well as temple architecture, woodcarving, and traditional dance in Thailand. This study employs a case-study approach, with data collected through participant observation, in-depth interviews, and document analysis. The findings indicate that mathematical practices such as geometry, proportion, symmetry, and patterns are consistently found in cultural artifacts and activities. The research results indicate that contextual learning incorporating ethnomathematics influences problem-solving abilities based on students’ levels of thinking. Additionally, this study provides insights into the interrelation between cultural values and mathematical symbolism. Cross-cultural analysis revealed common themes and significant differences in the application of mathematics, influenced by historical, religious, and environmental factors. The implications of this research include a deeper understanding of how culture shapes mathematical practices and how ethnomathematics can be integrated into education to enhance culturally relevant mathematics learning and improve students’ numeracy skills